ANALISIS TREND KINERJA PENGAJARAN DOSEN FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA MULAI TAHUN 2010 s.d 2015 - Achmad Fauzi; Petrolis Nusa Perdana; Dwi Handarini (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
Abstract Amid the college competition, where public universities are entering a new form of Public Service Agency (BLU), the public universities increasingly in demand to provide more quality services. Hence the focus on service improvement mainly lecturers teaching activities need to be improved from year to year.The better for its existence, the Faculty of Economics UNJ, should run higher education quality assurance has collected. then one way that can be achieved is by doing research on students regarding the level of student satisfaction on the performance of the teaching faculty of Economics diFakultas UNJ. The purpose of this study is to provide an overview of trends faculty performance and give impetus to occur padai improved performance in the coming years. The results of this study are brought average performance trend in the teaching faculty in each department is good, which is the average value moves above trend figures 3,0dengan the conclusion that the students of the Faculty of Economics satisfied with the performance of the teaching lecturer. Keywords: performance, performance measurement, customer satisfaction